2003
DOI: 10.1667/0033-7587(2003)160[0046:caicws]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Alterations in Cleanup Workers Sampled Years after the Chernobyl Accident

Abstract: Cytogenetic analysis performed 4-13 years after the Chernobyl accident showed an elevated frequency of acentrics, chromatid exchanges, dicentrics and rings in Chernobyl cleanup workers compared to the control group. Cytogenetic data were analyzed according to the information on exposure to radiation (the year when the cleanup workers worked at the Chernobyl station, doses rates, time elapsed since exposure to radiation, and cytogenetic examination) and some lifestyle factors. The data obtained suggested that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
8
0
3
Order By: Relevance
“…Effective doses depend on the time of arrival in the contaminated territory and the duration of exposure Snigiryova et al, 1997. Numerous studies have found that in most cases, the liquidators were exposed to low doses of ionizing radiation [Sevan,kaev et al 1995;Snigiryova et al, 1997;Moor et al, 1999;Domracheva et al, 2000;Neronova et al, 2003;Maznik and Vinnikov, 2005;Shevchenko and Snigiryova, 2006]. The current model of a threshold-free action of low-dose ionizing radiation unambiguously postulates that any level of irradiation presents a hazard.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Effective doses depend on the time of arrival in the contaminated territory and the duration of exposure Snigiryova et al, 1997. Numerous studies have found that in most cases, the liquidators were exposed to low doses of ionizing radiation [Sevan,kaev et al 1995;Snigiryova et al, 1997;Moor et al, 1999;Domracheva et al, 2000;Neronova et al, 2003;Maznik and Vinnikov, 2005;Shevchenko and Snigiryova, 2006]. The current model of a threshold-free action of low-dose ionizing radiation unambiguously postulates that any level of irradiation presents a hazard.…”
Section: Discussionmentioning
confidence: 66%
“…Examination of liquidators of the accident at the Chernobyl Nuclear Power Plant (ChNPP), either shortly after or many years following their irradiation, revealed increased levels of radiation-induced chromosome aberrations in their genomes as compared to unirradiated individuals [Sevan,kaev et al, 1995;Snigiryova et al, 1997;Moor et al, 1999;Domracheva et al, 2000;Neronova et al, 2003;Maznik and Vinnikov, 2005;Shevchenko and Snigiryova, 2006]. The possible genetic consequences of the ChNPP accident (hereditary and congenital malformations, spontaneous abortions, mortinatality) were estimated not to exceed 1% of the spontaneous rate [Bochkov and Chebotarev, 1989].…”
Section: Introductionmentioning
confidence: 99%
“…bystander effects) (Marozik et al. , 2007) and elevated chromosome alterations (Neronova et al. , 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The examination of liquidators of the accident at the ChNPP, either shortly after or many years following their irradiation, revealed increased levels of radiation-induced chromosome aberrations in their genomes as compared to unirradiated individuals (Sevankaev et al 1995;Snigiryova et al 1997;Domracheva et al 2000;Neronova et al 2003;Maznik et al 2003;Shevchenko and Snigireva 2006). In liquidators, a significant increase in incidence of solid cancers (Kashcheev et al 2015) with a latent period between 4 and 15 years is described (Ivanov et al 2009a, b).…”
Section: Unirradiated Children Born From Irradiated Parentsmentioning
confidence: 99%